2011
DOI: 10.1007/s13277-011-0155-8
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells and cancer therapy

Abstract: Cancer stem cells (CSCs) are a subpopulation of tumour cells that possess the stem cell properties of self-renewal and differentiation. Stem cells might be the target cells responsible for malignant transformation, and tumour formation may be a disorder of stem cell self-renewal pathway. Epigenetic alterations and mutations of genes involved in signal transmissions may promote the formation of CSCs. These cells have been identified in many solid tumours including breast, brain, lung, prostate, testis, ovary, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 169 publications
0
98
0
5
Order By: Relevance
“…CSCs possess the stem cell properties of self-renewal and differentiation; therefore, tumors may be initiated, grow, invade and metastasize (31). Anticancer therapies at present emphasize killing CSCs or inhibiting the induction of the CSC population (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSCs possess the stem cell properties of self-renewal and differentiation; therefore, tumors may be initiated, grow, invade and metastasize (31). Anticancer therapies at present emphasize killing CSCs or inhibiting the induction of the CSC population (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…CSCs are hypothesized to demonstrate resistance to chemo-and radiotherapy (31), and ABCG2 is a key regulator of chemoresistance (49). The results of the present study indicated that ABCG2 expression increased significantly while screening target proteins that were induced by treatment with TGF-β1, E2 and hypoxia ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to surface markers, CSCs share some key signaling pathways with normal stem cells which can be mutated in CSCs and be considered as attractive targets for cancer therapies (Soltanian and Matin, 2011). A distinguished understanding of signaling pathways between normal and CSCs is required to prevent destroying normal stem cells, as this is the key point to perfect accomplishment of anti-CSC therapies (Deonarain et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the major difference between cancer growth and normal tissue renewal is that whereas normal transit amplifying cells usually differentiate and die, at various levels of differentiation, the cancer transit-amplifying cells fail to differentiate normally and instead, accumulate (i.e. they undergo maturation arrest), resulting in cancer growth (Soltanian & Matin, 2011).…”
Section: Leukemia and Leukemic Developmentmentioning
confidence: 99%
“…Oct-4, a member of the family of POU-domain transcription factors, is expressed in pluripotent embryonic stem and germ cells. Oct-4 mRNA is normally found in totipotent and pluripotent stem cells of pregastrulation embryos (Soltanian & Matin, 2011). Expression of this factor plays a crucial role in maintaining the self-renewing, cancer stem-cell-like, and chemoradioresistant properties in lung cancer-derived CD133+ cells (Chen et al, 2008).…”
Section: Leukemia Stem Cells Characterizationmentioning
confidence: 99%